Recognizing the main signs and symptoms of diabetic ketoacidosis: an integrative review (Research, Society and Development, 2021)
Objective: to identify the main signs and symptoms of diabetic ketoacidosis evidenced in the scientific literature. Methodology: this is an integrative literature review, developed from May to June 2021. The search was performed through the journal portal Coordination for the Improvement of Higher Education Persons, in the following databases: Excerpta Medical data BASE, Medical Literature Analysis and Retrieval Online System and Latin American and Caribbean Literature in Health Sciences. The search strategy consisted of crossing the descriptors “Diabetic Ketoacidosis”, “Signs and Symptoms Diagnosis”, mediated by the Boolean operator “AND”. Articles published from 2017 to 2021 in Portuguese, English and Spanish were included. Gray literature studies and duplicate articles were excluded. Results: 423 studies were investigated, and of these, only seven met the eligibility criteria. Polydipsia, polyuria and weight loss were identified as the most frequent symptoms among patients diagnosed with diabetic ketoacidosis. As for recognition, there was a low level of identification of signs and symptoms of diabetic ketoacidosis by parents of children with diabetes mellitus and health professionals. As well, it was verified the influence of age and socioeconomic level on the prevalence of this endocrine emergency. Conclusion: a reduced recognition of signs and symptoms of diabetic ketoacidosis was noticed, in addition to the low specificity of the symptomatology of this complication, which makes diagnosis, control and monitoring difficult.